Evaluation of nature and intensity of fire concrete spalling by frequency analysis of sound records. (October 2021) - Mróz, Katarzyna; Hager, Izabela
Abstract: The paper presents a new method for identifying the form and intensity of spalling using an analysis of the acoustic signal emitted by concrete. To assess the intensity and monitor the course of concrete spalling during fire exposure, the analysis of the recorded sound from the furnace chamber is used. The spalling intensity was determined based on signal amplitude analysis. Investigation of sound records showed that the character of spalling can be categorized by a well-defined frequency value. Based on the analysis of the Fast Fourier Transform (FFT) spectrum, the authors have distinguished the following phenomena that are the source of the signal by assigning the corresponding frequency of the sound wave vibration: explosive spalling, aggregate spalling and destructive spalling. Highlights: Original sound-based NDT method to assess the spalling form and intensity within the time of the test is proposed. Frequency analysis of recorded sound provides a quantitative and qualitative assessment of concrete propensity to spalling. Nature of fire concrete spalling can be categorized by a well-defined frequency value. Waveform and spectrogram analysis delivers information on the exact number of spalling events within the performed test.